A simple Bird Sensitivity to Oil Index as a management tool in coastal and marine areas subject to oil spills when few biological information is available - Romero, A. F. [UNESP]; Oliveira, M. [UNESP]; Abessa, D. M.S. [UNESP] (Elsevier, 2018)
This study sought to develop a simple index for ranking birds' environmental sensitivity to oil in which birds are used as biological indicators. The study area consisted of both the Santos Estuarine System (SES), and the Laje de Santos Marine State Park (LSMSP), located in Southeastern Brazil. Information on the bird species and their feeding and nesting behaviors were obtained from the literature and were the basis of the sensitivity index created. The SES had a higher number of species, but only about 30% were found to be highly sensitive. The LSMSP presented a much lower number of species, but all of them were considered to be highly sensitive to oil. Due to its simplicity, this index can be employed worldwide as a decision-making tool that may be integrated into other management tools, particularly when robust information on the biology of birds is lacking.
Keywords: Behavior; Birds; ESI maps; Feeding; Nesting; Oil spill